2006
DOI: 10.4489/myco.2006.34.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Some Essential Oils Against Microorganisms Deteriorating Fruit Juices

Abstract: Seventeen microbial species including 10 fungal taxa, two yeasts and five bacteria, were isolated from freshly prepared orange, guava and banana juices kept in open bottles at room temperature for 7 days. Eight different essential oils, from local herbs, were tested for their antimicrobial activity against these test organisms. The essential oils of Cymbopogon citratus, Ocimum basilicum and Origanum majorana were found to be highly effective against these microorganisms. Aspergillus niger, A. flavus and Saccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
(62 reference statements)
3
19
1
1
Order By: Relevance
“…Both essential oils exhibited varying degrees of antifungal activities against Phytophthora species. The present data showed that C. citratus essential oil appear to be more toxic than O. basilicum essential oil against Phytophthora species (Table 4), which is in agreement with the results of other authors (Helal et al, 2006; Shadab et al, 1992). Essential oil of C. citratus showed potent inhibitory effect on the radial growth of P. capsici (91.9%), P. drechsleri (91.2%) and P. melonis (94.6%), as shown in Fig.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Both essential oils exhibited varying degrees of antifungal activities against Phytophthora species. The present data showed that C. citratus essential oil appear to be more toxic than O. basilicum essential oil against Phytophthora species (Table 4), which is in agreement with the results of other authors (Helal et al, 2006; Shadab et al, 1992). Essential oil of C. citratus showed potent inhibitory effect on the radial growth of P. capsici (91.9%), P. drechsleri (91.2%) and P. melonis (94.6%), as shown in Fig.…”
Section: Resultssupporting
confidence: 94%
“…It was effective in inhibiting fungal viability and spore germination, so morphological changes of fungal hyphae were observed under light microscope by essential oil of C. citratus (Sulaiman Ali Al Yousef, 2013). The essential oils of C. citratus and O. basilicum were found to be highly effective against A. niger , A. flavus and Saccharomyces cerevisiae , whereas C. citratus essential oil showed the strongest activity against these fungi (Helal et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils of mint are extensively used in toiletry, food and pharmaceutical industries because of its aromatic, stimulate and carminative nature (Karicheri and Antony, 2016). There is a relationship between the chemical structure of the most abundant compounds in the essential oil and the antimicrobial activity (Helal et al, 2006).Despite the beneficial effects of herbs, some microorganisms and their metabolites can be found which could lead to serious health problems. Among the microorganisms that may be present, moulds are the most relevant, mainly due to their mycotoxins production capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Citral has been used as a natural additive to food, cosmetics, and beverages due to its intense lemon aroma and flavor. (1, 2) Essential oils containing citral have been shown to exhibit antimicrobial, antifungal and antiparasitic properties,(3-7) making citral a natural preservative.…”
Section: Introductionmentioning
confidence: 99%